Sifat Mekanik Papan Komposit Berbahan Dasar Serat Sabut Kelapa Dan Serat Batang Pisang - Kosim Kosim; Wahyudi Wahyudi; Susilawati Susilawati; Aris Doyan (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2017)
Research on the manufacture of composite particle board based on natural fiber: coconut fiber (SSK) and banana fiber (SBP) by using PVAc matrix has been conducted. The purpose of this research is to get the physical and mechanical value of standard on composite board based on SNI03-2105-2006The research method is by taking the comparison of banana fiber reinforcing material (SBP) and coco fiber (SSK) in the form of particle size with composition ie (a) SBP 0%: SKK 100% (b) SBP 50%: SKK 50%, (c) SBP 80%: SSK 20, (d) SBP 60%: SSK 40%, (e) SBP 40%: SSK 60%, (f) SBP 20%: SKK 80%, and (g) SBP 100%: SSK 0%.All composite boards consist of 70 % Matrix and 30% fiber. The result of physical properties for density (ÃÂ) ranges from 0.54 gr / cm3 - 0.75 gr / cm3 and for water content (KA) ranges from 10.5% - 13.9%.As for the mechanical properties of the value of modulus rupture (MOR) ranged between 3483.44 kgf / cm2 - 7472,30 kgf / cm2 and elastic modulus value (MOE) ranged between 15981.23 kgf / cm2 - 27243,74 kgf / cm2. Based on the analysis of tredline graphs, both for physical and mechanical properties, it turns out for each composition of natural fibers to give different values.This means that the composition of the SSK-SBP mixture has an influence on the physical properties as well as the mechanical properties of the composite board. The quality of natural fiber-based composite board (SSK and SBP) both physical and mechanical properties have been in accordance with the standard reference SNI 03-02105-2006.